2014
DOI: 10.3233/nre-141105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the immediate effect of the training with a virtual reality game in stroke patients according side brain injury

Abstract: BACKGROUND: Stroke is a major cause of motor disability in adults and needs interventions that contribute to motor recovery. OBJECTIVE: This study aimed to compare the immediate effect of the training with virtual reality game in stroke patients according side brain injury. METHODS:The participants included 20 patients (10 right brain injury), mean age of 50.6 ± 9.2 years, and 20 healthy subjects of 50.9 ± 8.8 years. All participants made a kinematic evaluation of drinking a cup of water before and after train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Nearly half of the papers (17/41, 42%) recruited only stroke patients [ 22 , 35 - 50 ], 15% (6/41) recruited only healthy participants [ 51 - 56 ], and 17% (7/41) recruited both patients and healthy participants [ 23 , 30 , 57 - 61 ]. One paper recruited participants for a requirements-gathering phase but no details were provided regarding their health status and demographics [ 62 ], and 20% (8/41) of papers did not recruit any participants [ 63 - 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nearly half of the papers (17/41, 42%) recruited only stroke patients [ 22 , 35 - 50 ], 15% (6/41) recruited only healthy participants [ 51 - 56 ], and 17% (7/41) recruited both patients and healthy participants [ 23 , 30 , 57 - 61 ]. One paper recruited participants for a requirements-gathering phase but no details were provided regarding their health status and demographics [ 62 ], and 20% (8/41) of papers did not recruit any participants [ 63 - 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…For papers that recruited healthy subjects, combined standard deviation (39.9 years) was greater than the combined mean (37.3 years), indicative of how spread out the age ranges were. While 38% (9/24) of papers with patients did not record gender [ 23 , 44 - 47 , 57 , 59 , 60 , 70 ], the majority of patients in those that did were male and 2 had an equal distribution [ 39 , 48 ]. Meanwhile, 54% (7/13) of papers with healthy subjects did not record gender [ 52 , 53 , 55 - 57 , 59 , 60 ]; the majority of patients in those that did were male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Turning to stroke, several studies have explored uses of virtual reality in physiotherapy and/or occupational therapy [ 39 ]. Benefits have been described for upper and lower limb function, gait, and for everyday activities such as using a hammer or drinking from a cup [ 40 , 41 , 42 , 43 ]. Two meta analyses, comparing virtual reality treatments with conventional therapy, showed that results favoured the former [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%